2020
DOI: 10.1039/d0se00594k
|View full text |Cite
|
Sign up to set email alerts
|

An efficient bi-functional permselective separator coated with cubic type-Li7La3Zr2O12and activated carbon for lithium–sulfur batteries

Abstract: Controlling the shuttling of lithium polysulphides (LiPS) to enhance the utilization of elemental sulfur has been considered as an important issue to improve the energy density and coulombic efficiency of lithium–sulfur batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…2f). A similar observation was made by Natarajan et al, 55 and they reported that the R i value changed from 100 to 350 O in ten days.…”
Section: Characterization Of the Ceramic Separatorsupporting
confidence: 84%
See 3 more Smart Citations
“…2f). A similar observation was made by Natarajan et al, 55 and they reported that the R i value changed from 100 to 350 O in ten days.…”
Section: Characterization Of the Ceramic Separatorsupporting
confidence: 84%
“…In contrast, the R i value for the MAO/MWCNT separator remained around 90 O even after 9 days, indicating that MAO/ MWCNT acts as a scavenger to adsorb its traces solvents or impurities present in the electrolyte, thereby preventing their undesirable reactions with the Li metal anode. 55 Another possibility could be homogeneous electrolyte retention by the MAO/MWCNT matrix over Celgard s , thereby maintaining a constant R i , which is in line with the absorption property exhibited by MAO/MWCNT in the contact angle measurement. Thus, the fabricated freestanding MAO separator is observed to be highly stable with a Li metal interface.…”
Section: Characterization Of the Ceramic Separatormentioning
confidence: 73%
See 2 more Smart Citations
“…[33,34] For the S 2p peak (Figure 5g), the peak at 161.6, 163.0, 166.3, 168.4 and 169.5 eV are ascribed to the terminal sulfur atoms (S À 1 ), bridging sulfur atoms (S 0 ), SO 3 À , SO 4 À and SO x À 1 during the discharge mechanism, which could alleviate the sever shuttle problem. [35,36,37] Besides this, a new overlapped peak emerged at 163.5 eV, referring to the SÀ La chemical interactions. [38] Li 1s spectra for the cycled sample (Figure 5h) contained a broad signal that can be deconvoluted into two peaks at 55.4 eV and 56.3 eV.…”
Section: Chemistryselectmentioning
confidence: 99%